THE BANDUNG CITY SPATIAL PLANNING POLICIES IN GEOLOGICAL PERSPECTIVE - Sukiyah, Emi; Khoirullah, Nur (Journal of Geological Sciences and Applied Geology, 2020)
The Bandung city has an advantageous position, both from geographical, geological, political, and strategic aspects. The location of Bandung city, which is in the highlands, is famous for its cool weather. Since the colonial era of the Dutch East Indies, Bandung City has been the center of government and research in the field of geology. One piece of evidence that is still well preserved is the Geology Museum. Even the impression of geology is still strong with the many government institutions in the field of geological development in this city. The aspect of natural resources, including geology, is also the main asset to organize the Bandung city. The volcanic products that underlie this city become a fertile land for agriculture and the mining industry for construction and industrial materials. Several rivers also flow in this area. The hilly panorama with the post-volcanism phenomenon is an attraction for developers in the tourism sector. The groundwater potential is also abundant. The development of Bandung City does not mean that there are no obstacles. The significant increase in population has earned this city the nickname of the most populous city in West Java. If the city government cannot control the increase in the population density, it is not impossible that this city will be a city that does not have the appeal again. In fact, now the impact is already being felt, traffic jams, floods, waste, etc. Bandung city spatial planning should be carried out in an integrated manner, involving historical, geological, geographic, socio-cultural, political, and strategic aspects.